Planning and preparing for public health threats at airports - Greg Martin; Mairin Boland (BMC, 2018)
Abstract The ever-increasing speed and scope of human mobility by international air travel has led to a global transport network for infectious diseases with the potential to introduce pathogens into non-endemic areas, and to facilitate rapid spread of novel or mutated zoonotic agents. Robust national emergency preparedness is vital to mitigate the transmission of infectious diseases agents domestically and to prevent onward spread to other countries. Given the complex range of stakeholders who respond to an infectious disease threat being transmitted through air travel, it is important that protocols be tested and practised extensively in advance of a real emergency. Simulation exercises include the identification of possible scenarios based on the probability of hazards and the vulnerability of populations as a basis for planning, and provide a useful measure of preparedness efforts and capabilities. In October 2016, a live simulation exercise was conducted at a major airport in Ireland incorporating a public health threat for the first time, with the notification of a possible case of MERS-CoV aboard an aircraft plus an undercarriage fire. Strengths of the response to the communicable disease threat included appropriate public health risk assessment, case management, passenger information gathering, notification to relevant parties, and communication to passengers and multiple agencies. Lessons learned include: o Exercise planning should not be overly ambitious. In testing too many facets of emergency response, the public health response could be deprioritised. o The practical implementation of communication protocols in a real-time exercise of this scope proved challenging. These protocols should continue to be checked and tested by desk-top exercises to ensure that all staff concerned are familiar with them, especially in the context of staff turn-over. o The roles and responsibilities of the various agencies must be clear to avoid role confusion. o Equipment and infrastructure capacities must be considered and in place in advance of an actual incident or test, for example whether or not cell phone signals require boosting during a major event. Importantly, exercises bring together individuals representing organisations with different roles and perspectives allowing identification of capabilities and limitations, and problem solving about how to address the gaps and overlaps in a low-threat collaborative setting.